Reading the Hypertextuality of the Story of Abraham through Gérard Genette's Framework: An Analysis of QS. As-Saffat 99–113 and Al-Kitab 1–9 - Ika Rijqi Nafisah; Dian Nur Anna; Nur Aeni Putri Gafar (Lembaga Yasin AlSys, 2026)
This study examines the hypertextual relationship between the narrative of Prophet Ibrahim’s sacrifice in QS. As-Saffat 99–113 and Genesis 22:1–9 using Gérard Genette’s theory of hypertextuality. The study addresses the need for a comparative understanding of how sacred narratives within the Abrahamic tradition are related, transformed, and reinterpreted across different religious contexts. This research employed library research with descriptive-analytical and comparative approaches. Data were analyzed by identifying thematic similarities, narrative differences, and forms of transformation between the two texts. The findings show that both narratives share major themes, including divine command, obedience, the testing of faith, and sacrificial substitution. However, significant differences appear in the identity of the sacrificed son, narrative structure, dialogic elements, and theological emphasis. Through Genette’s hypertextuality framework, the two texts can be understood as interconnected narratives that undergo reinterpretation according to their respective religious traditions. The study concludes that religious texts are not isolated narratives but are connected through intertextual and hypertextual relationships within the Abrahamic tradition. These findings contribute to comparative scriptural studies by demonstrating how hypertextual analysis can reveal narrative continuity, transformation, and theological distinction between Qur’anic and Biblical accounts.